PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA PEMEGANNG KARTU MEMBER PASAR BUAH PEKANBARU - Agustina Anisa Nur; Zulkarnain Zulkarnain; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
fter deciding to become a member of a company, of course each customer will also have big expectations of the benefits or added value that will be received from the member card implementing company. One of the expectations is the existing services and facilities, with the existence of good services and facilities, the customer is less likely to switch to similar businesses or other competitors. The purpose of this study was to see the effect of service quality on customer satisfaction and loyalty to the Pekanbaru fruit market member card holder. This study uses a quantitative approach. The sample in this study amounted to 100 respondents aimed at the holder of the Pekanbaru fruit market members in Pekanbaru City, using a sampling technique. The research instrument used a questionnaire and analyzed using Path Analysis with the help of the SPSS version 23 program. The results of this study indicate that: 1) Service quality affects customer satisfaction at Pasar Buah Pekanbaru member card holder, 2) Service quality affects Customer Loyalty to Pasar Buah Pekanbaru member card holder, 3) Customer satisfaction affects Customer Loyalty of Pasar Buah Pekanbaru member card holders, 4) Service Quality affects Customer Satisfaction mediated by Customer Loyalty to the Pasar Buah Pekanbaru member card holder.Keywords: Service Quality, Customer Satisfaction, Customer Loyalty, Member Card Holders